Evaluation of the star family doctors training program: an observational cohort study of a novel continuing medical education program for general practitioners within a compact medical consortium: a quantitative analysis - Ling-Bo Liang; Xu Li; Xiang-Ping Liu; Cai-Zheng Li; Dan Luo; Feng Liu; Ting-Rui Mao; Qiao-Li Su (BMC Medical Education, 2023)
Introduction To determine the effectiveness of the Star Family Doctors Training Program, a comprehensive Continuing professional development (CPD) program for general practitioners (GPs) in a compact medical consortium. Patients and Methods Observational cohort study with a quantitative analyses in primary health care institutions in Sichuan Province. The interventions were as following: (1) The Star Family Doctors Training Program is a full-time, local government allocation program certified by the Health Department of Sichuan Province, emphasizing small group learning and practice, and using standard patients and medical patient simulators; 30 participants were selected by their institutions. (2) The control group underwent a self-financed after-work CPD program using conventional lectures; 50 participants were self-selected. Short-term effectiveness assessed using immediate post-training tests and self-evaluations; long-term (1 year) effectiveness evaluated using self-reported surveys. Results The study involved 80 GPs (28.75% men; mean age: 38.2 ± 9.2 years). The average post-training total score was higher in the STAR group than in the control group (72.83 ± 5.73 vs. 68.18 ± 7.64; p = 0.005). Compared to the controls, STAR participants reported seeing more patients (all p < 0.05), and had more patients who signed family-doctor contracts (p = 0.001) as well as increased patient satisfaction (p = 0.03), respectively. STAR-group trainees appraised the program higher and were more willing to recommend it to colleagues (90% vs. 64%, p = 0.011). Conclusion The Star Family Doctors Training Program achieved good responses and provides a reference for future CPD programs.